2005
DOI: 10.1111/j.1365-4632.2005.02633.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of keloids and hypertrophic scars with dermojet injections of bleomycin: a preliminary study

Abstract: Intralesional jet injection of bleomycin is an effective and safe method of treating keloids and hypertrophic scars that are unresponsive to intralesional steroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 32 publications
7
125
1
3
Order By: Relevance
“…After administering three to five intralesional injections of bleomycin within a 1-month period, the authors observed complete regression in 69.4% of the keloids. Subsequent studies revealed similar results, with significant improvement in hypertrophic scar and keloid height and pliability as well as reduction in erythema, pruritus and pain (135,137,138). Occasionally, development of hyperpigmentation and dermal atrophy may occur with bleomycin treatment.…”
Section: Current Treatment Strategiessupporting
confidence: 54%
“…After administering three to five intralesional injections of bleomycin within a 1-month period, the authors observed complete regression in 69.4% of the keloids. Subsequent studies revealed similar results, with significant improvement in hypertrophic scar and keloid height and pliability as well as reduction in erythema, pruritus and pain (135,137,138). Occasionally, development of hyperpigmentation and dermal atrophy may occur with bleomycin treatment.…”
Section: Current Treatment Strategiessupporting
confidence: 54%
“…The recommended dosage starts at 0.1 ml (1.5 IU/ml) and can go up to a maximum dose of 6 ml in order to prevent adverse effects which are usually cutaneous and less common pulmonary. 31,32 For patients with old scars that do not respond to intralesional steroid, the recommended treatment is between 2 and 6 sessions per month. Bleomycin usage is still uncommon in the clinical practice.…”
Section: Bleomycinmentioning
confidence: 99%
“…Mögliche Nebenwirkungen sind Hautirritationen, Schmerzen während der Injektion, Ulzerationen und Purpura. Auch über intraläsionales Bleomycin existieren durchaus positi− ve Studienergebnisse [24,25]. Durch ein ¹Einpricken" der Sub− stanz, d. h. externes Auftragen und anschließende Punktion mit einer Nadel, findet eine geringere Resorption statt.…”
Section: Intraläsionale Zytostatikaunclassified